The Increased Business of Edged Weapon Without Authorizations via Social Media in Gorontalo Province - I Komang Kris Kamisma; Moh. Taufik Zulfikar Sarson; Amanda Adelina Harun (Estudiante Law Journal, 2022)
This study aims to find out and analyze how the role of the police in dealing with cases of selling sharp weapons without a permit through social media, as well as to find out the obstacles in the process of handling these cases. This type of research is empirical research with a descriptive approach. Data obtained directly through observations and interviews from the Gorontalo Provincial Police, and data obtained directly through social media. The results of the study show that there has been no action against the perpetrators of selling sharp weapons on social media which is actually a criminal act as regulated by law. This is one proof that law enforcement in Indonesia, especially in the matter of criminal acts committed in social media or cyberspace, is not implemented properly. The lack of supervision and seriousness of law enforcers in implementing the law is the cause of many cases that are not handled.As for the obstacles in law enforcement against the case in question due to the lack of experts in the cyber field, weak government supervision in the virtual field, people who do not understand and care, as well as the limitations of laws that discuss and regulate criminal acts of selling sharp weapons, especially through social media.